O professor de português língua estrangeira como interculturalista em contexto de extensão universitária - Jesus, Isabela Abê de [UNESP] (2015)
This investigation handles the teacher as an interculturalist in a multicultural context of teaching and learning Portuguese as a Foreign Language (PFL) (ALMEIDA FILHO, 2001, 2004, 2007, 2009; CUNHA, 2007; KFOURI-KANEOYA, 2008, 2013, 2015; SERRANI, 2005; MENDES, 2003, 2004a, 2011). The study aimed at investigating how the participant teacher explores the intercultural aspects that permeate the learning and teaching process of PFL; and observe the contributions of the interculturality in this context to the education of PFL teacher as an interculturalist (SERRANI, 2005). Two questions and a sub question were proposed. The first research question had the purpose of analyzing how the participant teacher explores interculturalism in class, and the sub question related to it had the intention to discuss the conceptions of culture revealed in the teacher's sayings and doings; by its turn the second research question had as its objective to discuss how interculturalism present in the investigated context can contribute to the education of PFL teacher as an interculturalist. The research study has two focuses: the first are the teaching practices of a teacher in a class of a regular course of PFL at UNESP (São José do Rio Preto), at the level of beginners, in which the learners are undergraduate and post-graduate students in a situation of academic immersion, coming from partner foreign universities of the Brazilian institution; the second focus is on the participation of the same teacher in the weekly meetings of the education, research and teaching group of the extension project in which the regular course is inserted. According to a qualitative study of ethnographic nature (ANDRÉ, 2000; RICHARDS, 2003) and with characteristics of collaborative research, the data were generated through (i) audio recordings of PFL lessons taught by the participant teacher; (ii) audio recordings of the meetings of the formation, research and teaching ...